The Application of Moist Exposed Burn Ointment (MEBO) and Binahong Leaves in Treating Partial Thickness Burn : A Case Report - Prasetyo, Arif Tri; Heridadi, Eko (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Burn healing is dependent on good wound care management. Infection is one of the cause of wound healing failure. Infectious wound should be treated immediately. Binahong’s leaves is trusted as traditional herbal medicine which is considered capable to help wound healing process. Patient and Method: A 35 years old women suffer from scald and got 3% surface partial thickness burn at her right hand. The patient was initialy treated by application of MEBO. After a week patient came and felt uncomforted with the gauze. So, binahong’s leaves was patched on her wound to help the wound healing process. Result: After a week with binahong’s leaves therapy, the epithelialization is good and there was no infection. The result is satisfactory. Conclusion: This study shows that binahong’s leaves can be used to help wound healing process.